FIB-SEM investigation of trapped intermetallic particles in anodic oxide films on AA1050 aluminium - M. Jariyaboon (2018)
Purpose: The purpose of this investigation is to understand the structure of trapped intermetallics particles and localized composition changes in the anodized anodic oxide film on AA1050 aluminium substrates. Design/methodology/approach: The morphology and composition of Fe-containing intermetallic particles incorporated into the anodic oxide films on industrially pure aluminium (AA1050, 99.5 per cent) has been investigated. AA1050 aluminium was anodized in a 100 ml/l sulphuric acid bath with an applied voltage of 14 V at 20°C ±2°C for 10 or 120 min. The anodic film subsequently was analyzed using focused ion beam-scanning electron microscopy (FIB-SEM), SEM, and EDX. Findings: The intermetallic particles in the substrate material consisted of Fe or both Fe and Si with two different structures: irregular and round shaped. FIB-SEM cross-sectioned images revealed that the irregular-shaped particles were embedded in the anodic oxide film as a thin strip structure and located near the top surface of the film, whereas the round-shaped particles were trapped in the film with a spherical structure, but partially dissolved and were located throughout the thickness of the anodic film. The Fe/Si ratio of the intermetallic particles decreased after anodizing. Originality/value: This paper shows that dual beam FIB-SEM seems to be an easy, less time consuming and useful method to characterize the cross-sectioned intermetallic particles incorporated in anodic film on aluminium. © Emerald Group Publishing Limited.